2023
DOI: 10.1002/cbf.3789
|View full text |Cite
|
Sign up to set email alerts
|

Acid sphingomyelinase (ASM) and COVID‐19: A review of the potential use of ASM inhibitors against SARS‐CoV‐2

Abstract: In the last 2 years, different pharmacological agents have been indicated as potential inhibitors of SARS-CoV-2 in vitro. Specifically, drugs termed as functional inhibitors of acid sphingomyelinase (FIASMAs) have proved to inhibit the SARS-CoV-2 replication using different types of cells. Those therapeutic agents share several chemical structure characteristics and some well-known representatives are fluoxetine, escitalopram, fluvoxamine, and others. Most of the FIASMAs are primarily used as effective therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…In particular, analysis of data obtained in in silico, in vitro, or in vivo studies suggested the use of 49 FIASMAs in the treatment of SARS-CoV-2 infection, although outcomes from randomized double-blind clinical trials are available only for amlodipine and fluvoxamine [98]. Moreover, recent findings also suggested antidepressants involved in SL-controlled autophagy (a cellular catabolic process leading to lysosomal degradation and recycling of proteins and organelles) linked to lysosomal proton pump (ATP-ase) inactivation and block of extracellular Cer-rich domain formation [99,100].…”
Section: Sphingolipids As Potential Therapeutic Targets In Sars-cov-2...mentioning
confidence: 99%
“…In particular, analysis of data obtained in in silico, in vitro, or in vivo studies suggested the use of 49 FIASMAs in the treatment of SARS-CoV-2 infection, although outcomes from randomized double-blind clinical trials are available only for amlodipine and fluvoxamine [98]. Moreover, recent findings also suggested antidepressants involved in SL-controlled autophagy (a cellular catabolic process leading to lysosomal degradation and recycling of proteins and organelles) linked to lysosomal proton pump (ATP-ase) inactivation and block of extracellular Cer-rich domain formation [99,100].…”
Section: Sphingolipids As Potential Therapeutic Targets In Sars-cov-2...mentioning
confidence: 99%
“…This interferes with intracellular endolyosomal viral trafficking. 17 Although many drugs are classified as FIASMAs, and some of the earlier research focussed on the closely related compound fluvoxamine, fluoxetine, which is on the WHO's list of Essential Medications, 18 was found to have the greatest in vitro FIASMA activity, the best tolerability profile, and the most favourable pharmacokinetic properties. 19 In vitro anti-SARS-CoV-2 activity has been shown at fluoxetine concentrations approximating those during the treatment of depression (20 mg daily; 0.8 µg/ml, 2.6 µM).…”
Section: Introductionmentioning
confidence: 99%